Solid electrolytic capacitor and method of manufacturing same

By limiting the molar ratio of cationic components in the electrolyte layer to 23 or less, the capacitors maintain low ESR and thermal stability, addressing the issue of dedoping reactions under thermal stress.

JP7616313B2Active Publication Date: 2025-01-17NIPPON CHEMI CON CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023176781
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-09-21
Filing Date
2023-10-12
Publication Date
2025-01-17
Estimated Expiration
2039-09-13

AI Technical Summary

Technical Problem

Solid electrolytic capacitors experience a rapid increase in equivalent series resistance (ESR) due to dedoping reactions of the dopant under thermal stress, which is not effectively addressed by existing methods.

Method used

The capacitors are designed with a specific molar ratio of cationic components, such as ammonia, in the electrolyte layer, limited to 23 or less relative to the functional groups that can contribute to the doping reaction, to stabilize the ESR under thermal stress.

Benefits of technology

This design effectively suppresses dedoping reactions, maintaining low ESR even after thermal stress, enhancing the capacitors' thermal stability and conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616313000006
    Figure 0007616313000006
  • Figure 0007616313000007
    Figure 0007616313000007
  • Figure 0007616313000008
    Figure 0007616313000008
Patent Text Reader

Abstract

To provide a solid electrolytic capacitor having an electrolyte layer composed of a solid electrolyte layer and a liquid, in which a de-doping reaction is suppressed and particularly, ESR does not easily rise rapidly even after the capacitor has been subjected to a thermal stress load.SOLUTION: In the solid electrolytic capacitor, an electrolyte layer is formed in a capacitor element that is formed of an anode foil and a cathode foil which oppose each other. This electrolyte layer includes a solid electrolyte layer and liquid. The solid electrolyte layer contains an electroconductive polymer composed of a dopant and a conjugated polymer. The liquid is filled in a hollow portion in the capacitor element in which the solid electrolyte layer is formed. The electrolyte layer contains ammonia as a cation component; and a molar ratio of the cation component to 1 mole of a functional group is 23 or less, which can contribute to a doping reaction of the dopant.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid electrolytic capacitor. And its manufacturing method Regarding. [Background technology]

[0002] Electrolytic capacitors using valve metals such as tantalum or aluminum can achieve a small size and large capacity by expanding the surface area of ​​the dielectric by forming the valve metal as the anode electrode into a sintered body or etched foil, etc. In particular, solid electrolytic capacitors, in which a dielectric oxide film is covered with a solid electrolyte, are small in size, have a large capacity, and have a low equivalent series resistance, making them indispensable for miniaturizing electronic devices, improving their functionality, and reducing their costs.

[0003] Known examples of solid electrolytes include manganese dioxide and 7,7,8,8-tetracyanoquinodimethane (TCNQ) complexes. In recent years, conductive polymers derived from monomers with π-conjugated double bonds, such as poly(3,4-ethylenedioxythiophene) (PEDOT), which has a slow reaction rate and excellent adhesion to dielectric oxide films, have rapidly become popular as solid electrolytes. Polyanions such as organic sulfonic acids are used as dopants in conductive polymers during chemical oxidative polymerization or electrolytic oxidative polymerization, resulting in high conductivity.

[0004] However, compared to liquid-type electrolytic capacitors, in which the capacitor element is impregnated with an electrolytic solution and no solid electrolyte layer is used, solid electrolytic capacitors are poor at repairing defects in the dielectric oxide film, and there is a risk of increased leakage current. Therefore, so-called hybrid-type solid electrolytic capacitors, in which a solid electrolyte layer is formed on a capacitor element in which an anode foil and a cathode foil are opposed to each other, and the gaps in the capacitor element are impregnated with an electrolytic solution, have attracted attention.

[0005] This hybrid type solid electrolytic capacitor is also attracting attention because its equivalent series resistance (ESR) is not easily affected by the electrical conductivity of the electrolyte. In general, the ESR of an electrolytic capacitor that uses only an electrolyte is easily affected by the electrical conductivity of the electrolyte, and the lower the electrical conductivity of the electrolyte, the higher the ESR tends to be. However, the ESR of a solid electrolytic capacitor that includes a solid electrolyte layer and an electrolyte is not easily affected by the electrical conductivity of the electrolyte. In other words, even if the electrical conductivity of the electrolyte is low, the ESR of the product can be sufficiently small. The reason for this is that the electrical conductivity of the conductive polymer used in the solid electrolytic capacitor is orders of magnitude higher than that of the electrolyte, and the electrical conductivity of the conductive polymer has a large effect on the ESR. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP2006-114540 Summary of the Invention [Problem to be solved by the invention]

[0007] However, in solid electrolytic capacitors using both a solid electrolyte and an electrolytic solution, the conductivity deteriorates due to the dedoping reaction of the dopant, and the ESR of the solid electrolytic capacitor increases. In response to the increase in ESR caused by the dedoping reaction, Patent Document 1 reports that the dedoping reaction can be suppressed by making the molar ratio of the acid component and the base component, which are solute components in the electrolytic solution, acid excess. This report presumes that the dedoping reaction is suppressed because the dopant, which is an acid component, and the acid component in the electrolytic solution maintain an equilibrium state.

[0008] However, solid electrolytic capacitors may be subjected to thermal stress when used in high-temperature environments (e.g., 115°C or higher) or during the reflow soldering process when mounting solid electrolytic capacitors on circuit boards, etc. This thermal stress promotes the de-doping reaction even if the solute components in the electrolyte are in excess of acid. Therefore, the ESR of solid electrolytic capacitors rises sharply after thermal stress is applied.

[0009] The present invention has been proposed to solve the above problems, and its object is to provide a solid electrolytic capacitor having a solid electrolyte and a liquid electrolyte, in which the ESR is unlikely to increase rapidly even after thermal stress is applied. And its manufacturing method The purpose of this invention is to provide [Means for solving the problem]

[0010] The present inventors prepared solid electrolytic capacitors with a fixed amount of cationic components and a changed amount of anionic components, and with a fixed amount of anionic components and a changed amount of cationic components, respectively, and performed a reflow process to apply thermal stress to these solid electrolytic capacitors, and measured the ESR before and after the thermal stress. The results on the far left side of FIG. 1 (shown as "Cation only" in FIG. 1) are those in which the anionic component azelaic acid was not added, but only the cationic component triethylamine was added. As a result, as shown in FIG. 1, the ESR changes before and after the thermal stress of each solid electrolytic capacitor with a fixed amount of cationic components showed almost the same tendency, whereas the solid electrolytic capacitors with a fixed amount of anionic components showed large and small ESR changes before and after the thermal stress. From these results, the present inventors have found that the change in ESR occurring before and after the thermal stress is determined by the amount of cationic components contained in the electrolyte layer, rather than by the influence of pH or the influence of the acid-base ratio.

[0011] The solid electrolytic capacitor of the present invention has been made based on this finding, and comprises a capacitor element formed of an anode foil and a cathode foil facing each other, and an electrolyte layer formed in the capacitor element, the electrolyte layer having a solid electrolyte layer containing a dopant and a conjugated polymer, and a liquid filled in voids in the capacitor element in which the solid electrolyte layer is formed, the electrolyte layer containing ammonia as a cationic component, and a molar ratio of the cationic component to 1 mol of functional groups that can contribute to a doping reaction of the dopant is 23 or less.

[0012] The cationic component may be contained only in the liquid, and the molar ratio of the cationic component to 1 mol of the functional group may be 23 or less.

[0013] The cationic component may be contained only in the solid electrolyte layer, and the molar ratio of the cationic component to 1 mol of the functional group may be 23 or less.

[0014] The electrolyte layer may include cationic components in both the solid electrolyte layer and the liquid, the cationic components included in the liquid may include ammonia, and the solid electrolyte layer may include the cationic component different from ammonia, and a molar ratio of the cationic components to 1 mol of functional groups that can contribute to a doping reaction of the dopant, in total, of the cationic components included in the solid electrolyte layer and the liquid may be 23 or less. Another aspect of the present invention is a method for manufacturing a solid electrolytic capacitor, the method including the steps of: forming a capacitor element by placing an anode foil and a cathode foil opposite each other; and forming an electrolyte layer in the capacitor element, the step of forming the electrolyte layer including a step of forming a solid electrolyte layer containing a dopant and a conjugated polymer; and a step of filling a void in the capacitor element in which the solid electrolyte layer has been formed with a liquid, the method including the steps of: containing cationic components in both the solid electrolyte layer and the liquid; containing ammonia in the cationic component; containing the solid electrolyte layer including the cationic component different from ammonia; and setting the molar ratio of the cationic components to 1 mol of functional groups that can contribute to a doping reaction of the dopant to 23 or less by combining the cationic components in the solid electrolyte layer and the liquid. The electrolyte layer may contain ammonia as a cationic component, and the cationic component may be contained in both the solid electrolyte layer and the liquid, and the molar ratio of the cationic component to 1 mol of functional groups that can contribute to the doping reaction of the dopant may be set to 23 or less by adding up the cationic components contained in the solid electrolyte layer and the liquid.

[0015] The electrolyte layer may contain the cationic component at a molar ratio of the cationic component to 1 mol of the functional group of 11.4 or less.

[0016] The electrolyte layer may contain the cationic component in a molar ratio of 6 or less to 1 mol of the functional group.

[0017] The ammonia may be contained in the electrolyte layer at a molar fraction of 0.1 or more of all cationic components in the electrolyte layer.

[0018] The ammonia may be contained in the electrolyte layer at a molar fraction of 0.5 or more of all cationic components in the electrolyte layer.

[0019] The dopant may be polystyrene sulfonic acid.

[0020] The liquid may include ethylene glycol.

[0021] The ethylene glycol may be contained in the liquid at 50 wt % or more. Effect of the Invention

[0022] According to the present invention, in a solid electrolytic capacitor using a solid electrolyte and a liquid in combination, the de-doping reaction of a conjugated polymer can be suppressed to achieve a good ESR, and since the thermal stability is high, an increase in ESR after thermal stress can be suppressed. [Brief description of the drawings]

[0023] [Figure 1] 1 is a graph showing the relationship between the ratio of anion (acid) components to cation (base) components contained in the liquid and the change in ESR before and after reflow. [Diagram 2] 1 is a graph showing the relationship between ESR before and after reflow and the molar ratio of ammonia to 1 mol of functional groups that can contribute to the doping reaction of a dopant. [Diagram 3] 1 is a graph showing the relationship between ESR before and after reflow and the molar ratio of ammonia to 1 mol of functional groups that can contribute to the doping reaction of a dopant. [Figure 4] 1 is a graph showing the relationship between ESR before and after reflow and the molar ratio of the cationic components, which are the sum of ammonia and sodium hydroxide, to 1 mol of a functional group that can contribute to a doping reaction of a dopant. [Diagram 5] 1 is a graph showing the relationship between ESR before and after reflow and the molar ratio of ammonia to 1 mol of functional groups that can contribute to the doping reaction of a dopant. [Figure 6] 1 is a graph showing the relationship between ESR after reflow and the molar fraction of ammonia in the cationic components of the electrolyte. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Hereinafter, a solid electrolytic capacitor according to an embodiment of the present invention will be described. The solid electrolytic capacitor may have, for example, a wound type or a laminated type. In this embodiment, a wound type is described as an example, but the solid electrolytic capacitor of the present invention is not limited to this, and is not limited to other embodiments described.

[0025] A solid electrolytic capacitor is a passive element that stores and discharges electric charge by capacitance, and is a so-called hybrid type solid electrolytic capacitor that uses both a solid electrolyte layer and a liquid. Hereinafter, the hybrid type solid electrolytic capacitor will be referred to simply as a solid electrolytic capacitor.

[0026] A wound-type solid electrolytic capacitor is constructed by inserting a cylindrical capacitor element into a bottomed cylindrical exterior case, attaching a rubber seal to the open end of the exterior case, and sealing the open end by crimping. An electrolyte layer is formed in the capacitor element, and an anode lead and a cathode lead are connected to the anode foil and cathode foil, respectively, and the anode lead and cathode lead are pulled out from the rubber seal.

[0027] In such a solid electrolytic capacitor, the capacitor element is formed by winding an anode foil and a cathode foil with a separator interposed therebetween. A dielectric oxide film layer is formed on the surface of the anode foil. The electrolyte layer includes a solid electrolyte layer and a liquid. The solid electrolyte layer is formed so as to cover at least a portion of the dielectric oxide film layer on the surface of the anode foil. The liquid fills the voids of the capacitor element in which the solid electrolyte layer is formed.

[0028] (electrode foil) The anode foil and cathode foil are long foils made of valve metals such as aluminum, tantalum, niobium, niobium oxide, titanium, hafnium, zirconium, zinc, tungsten, bismuth, and antimony. The purity of the anode foil is preferably 99.9% or more, and that of the cathode foil is preferably 99% or more, but impurities such as silicon, iron, copper, magnesium, and zinc may be included.

[0029] The anode foil and the cathode foil have a porous structure on the surface as a sintered body obtained by sintering a powder of a valve metal, or as an etched foil obtained by etching a stretched foil. The porous structure is composed of tunnel-like pits, spongy pits, or voids between densely packed powder particles. The porous structure is typically formed by direct current etching or alternating current etching in an acidic aqueous solution containing halogen ions such as hydrochloric acid, or by vapor deposition or sintering metal particles or the like on the core. The cathode foil may be subjected to an etching process.

[0030] The dielectric oxide film layer is the dielectric layer of the solid electrolytic capacitor, and is typically an oxide film formed on the surface layer of the anode foil. If the anode foil is made of aluminum, the dielectric oxide film layer is an aluminum oxide layer obtained by oxidizing the porous structure region. This dielectric oxide film layer is formed by applying a voltage in a solution that does not contain halogen ions, such as an aqueous solution of adipic acid or boric acid. The cathode foil may also be formed with a thin dielectric oxide film layer as necessary, and may further include a layer made of metal nitride, metal carbide, or metal carbonitride formed by vapor deposition, or may include carbon on the surface. The dimensions of the anode foil and the cathode foil can be set arbitrarily according to the specifications of the solid electrolytic capacitor to be manufactured.

[0031] (Solid electrolyte layer) The solid electrolyte layer contains a conjugated polymer and a dopant. A conjugated polymer or a doped conjugated polymer is also called a conductive polymer. A conjugated polymer is obtained by chemical oxidative polymerization or electrolytic oxidative polymerization of a monomer having a π-conjugated double bond or a derivative thereof. By performing a doping reaction on a conjugated polymer, the conductive polymer exhibits high conductivity.

[0032] The conjugated polymer may be any known polymer without any particular limitation. For example, polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene, polyphenylene, polyphenylenevinylene, polyacene, polythiophenevinylene, etc. These conjugated polymers may be used alone, or in combination of two or more kinds, or may be a copolymer of two or more kinds of monomers.

[0033] Among the above conjugated polymers, conjugated polymers formed by polymerizing thiophene or its derivatives are preferred, and conjugated polymers formed by polymerizing 3,4-ethylenedioxythiophene (i.e., 2,3-dihydrothieno[3,4-b][1,4]dioxine), 3-alkylthiophene, 3-alkoxythiophene, 3-alkyl-4-alkoxythiophene, 3,4-alkylthiophene, 3,4-alkoxythiophene, or derivatives thereof are preferred. As the thiophene derivative, a compound selected from thiophenes having substituents at the 3rd and 4th positions is preferred, and the substituents at the 3rd and 4th positions of the thiophene ring may form a ring together with the carbons at the 3rd and 4th positions. The carbon number of the alkyl group or alkoxy group is preferably 1 to 16, and in particular, a polymer of 3,4-ethylenedioxythiophene called EDOT, i.e., poly(3,4-ethylenedioxythiophene) called PEDOT is particularly preferred. Also usable are alkylated ethylenedioxythiophenes in which an alkyl group is added to 3,4-ethylenedioxythiophene, such as methylated ethylenedioxythiophene (i.e., 2-methyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine) and ethylated ethylenedioxythiophene (i.e., 2-ethyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine).

[0034] The dopant may be any known dopant without any particular limitation. For example, inorganic acids such as boric acid, nitric acid, and phosphoric acid, and organic acids such as acetic acid, oxalic acid, citric acid, ascot acid, tartaric acid, squaric acid, rhodizonic acid, croconic acid, salicylic acid, p-toluenesulfonic acid, 1,2-dihydroxy-3,5-benzenedisulfonic acid, methanesulfonic acid, trifluoromethanesulfonic acid, borodisalicylic acid, bisoxalateborate acid, sulfonylimide acid, dodecylbenzenesulfonic acid, propylnaphthalenesulfonic acid, and butylnaphthalenesulfonic acid may be mentioned. In addition, examples of polyanions include polyvinylsulfonic acid, polystyrenesulfonic acid, polyallylsulfonic acid, polyacrylicsulfonic acid, polymethacrylic acid, poly(2-acrylamido-2-methylpropanesulfonic acid), polyisoprenesulfonic acid, polyacrylic acid, polymethacrylic acid, and polymaleic acid. The dopant may be used alone or in combination of two or more kinds. Alternatively, a polymer or a monomer may be used.

[0035] The number average molecular weight of the polyanion is 1,000 to 2,000,000, and preferably 10,000 to 500,000. If the number average molecular weight is less than 1,000, the conductivity of the resulting conductive polymer is insufficient and dispersibility is reduced, which is not preferable, whereas if the number average molecular weight exceeds 2,000,000, the viscosity of the mixed liquid increases, which is not preferable.

[0036] This solid electrolyte layer can be obtained by, for example, adding a monomer, an acid or an alkali metal salt thereof that releases a dopant, and an oxidizing agent, stirring until chemical oxidative polymerization is completed, and then removing the oxidizing agent and residual monomers by purification means such as ultrafiltration, cation exchange, and anion exchange. As the oxidizing agent, trivalent iron salts such as p-toluenesulfonate iron(III), naphthalenesulfonate iron(III), anthraquinonesulfonate iron(III), or peroxodisulfate salts such as peroxodisulfate, ammonium peroxodisulfate, and sodium peroxodisulfate can be used, and a single compound or two or more compounds may be used. There is no strict limit to the polymerization temperature, but it is generally in the range of 10 to 60°C. The polymerization time is generally in the range of 10 minutes to 30 hours.

[0037] In addition, this solid electrolyte layer can also be obtained by, for example, adding a monomer and an acid or an alkali metal salt thereof that releases a dopant, carrying out electrolytic oxidation polymerization while stirring, and then removing the residual monomer by a purification means such as ultrafiltration, cation exchange, and anion exchange, to obtain a mixed solution. The electrolytic oxidation polymerization is carried out by any of the constant potential method, constant current method, and potential sweep method. In the case of the constant potential method, a potential of 1.0 to 1.5 V with respect to a saturated calomel electrode is suitable, and in the case of the constant current method, a potential of 1 to 10,000 μA / cm is suitable. 2 In the case of a potential sweep method, it is preferable to sweep in the range of 0 to 1.5 V against a saturated calomel electrode at a rate of 5 to 200 mV / sec. There is no strict limit to the polymerization temperature, but it is generally in the range of 10 to 60°C. The polymerization time is generally in the range of 10 minutes to 30 hours.

[0038] The method for forming the solid electrolyte layer is not particularly limited, and for example, the solid electrolyte layer can be formed by impregnating a dispersion liquid containing particles or powder of a conductive polymer into a capacitor element and attaching the conductive polymer to a dielectric oxide film layer. In order to promote impregnation into the capacitor element, a decompression treatment or a pressurization treatment may be performed as necessary. The impregnation process may be repeated multiple times. The solvent of the dispersion liquid of the conductive polymer is evaporated and removed by drying as necessary. Heat drying or reduced pressure drying may be performed as necessary.

[0039] The solvent for the conductive polymer dispersion may be any solvent capable of dispersing conductive polymer particles or powder, such as water, an organic solvent, or a mixture thereof. Suitable examples of the organic solvent include polar solvents such as N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethylsulfoxide; alcohols such as methanol, ethanol, propanol, and butanol; esters such as ethyl acetate, propyl acetate, and butyl acetate; hydrocarbons such as hexane, heptane, benzene, toluene, and xylene; carbonate compounds such as ethylene carbonate and propylene carbonate; ether compounds such as dioxane and diethyl ether; chain ethers such as ethylene glycol dialkyl ether, propylene glycol dialkyl ether, polyethylene glycol dialkyl ether, and polypropylene glycol dialkyl ether; heterocyclic compounds such as 3-methyl-2-oxazolidinone; and nitrile compounds such as acetonitrile, glutarodinitrile, methoxyacetonitrile, propionitrile, and benzonitrile.

[0040] A cationic component may be added to a dispersion liquid containing a conductive polymer consisting of a conjugated polymer and a dopant. The cationic component to be added to a dispersion liquid containing a conductive polymer is not particularly limited, and examples thereof include inorganic alkalis such as sodium hydroxide, potassium hydroxide, calcium hydroxide, and ammonia, aliphatic amines such as ethylamine, diethylamine, methylethylamine, and triethylamine, aromatic amines such as aniline, benzylamine, pyrrole, imidazole, and pyridine, and derivatives thereof, nitrogen-containing compounds such as N-methyl-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, hexamethylphosphortriamide, N-vinylpyrrolidone, N-vinylformamide, and N-vinylacetamide, sodium alkoxides such as sodium methoxide and sodium ethoxide, metal alkoxides such as potassium alkoxide and calcium alkoxide, and organic alkalis such as dimethyl sulfoxide. These cationic components may be used alone or in combination of two or more.

[0041] Furthermore, the conductive polymer dispersion may contain a polyhydric alcohol. Examples of the polyhydric alcohol include sorbitol, ethylene glycol, diethylene glycol, triethylene glycol, polyoxyethylene glycol, glycerin, polyoxyethylene glycerin, xylitol, erythritol, mannitol, dipentaerythritol, pentaerythritol, and combinations of two or more of these. Since the polyhydric alcohol has a high boiling point, it can remain in the solid electrolyte layer even after the drying process, and the effect of reducing ESR and improving voltage resistance can be obtained. Furthermore, other compounds may be contained. For example, conventional additives such as organic binders, surfactants, defoamers, coupling agents, antioxidants, and ultraviolet absorbers may be added. It is also possible to significantly reduce the ESR by adding additives to the conductive polymer dispersion or increasing the number of times the conductive polymer dispersion is impregnated into the capacitor element.

[0042] (liquid) The liquid is filled into the voids of the capacitor element in which the solid electrolyte layer is formed. The liquid may be impregnated to the extent that the solid electrolyte layer swells. In the liquid impregnation step, a depressurization treatment or a pressurization treatment may be performed as necessary. The liquid is one or a mixture of two or more of the various solvents listed below. This liquid is used as a solvent and may contain a solute or additive described below. A liquid containing a solute described below is also called an electrolyte.

[0043] First, the solvent may be a protic organic polar solvent or an aprotic organic polar solvent, either alone or in combination of two or more. The solute may be an anion component or a cation component. The solute is typically a salt of an organic acid, a salt of an inorganic acid, or a salt of a complex compound of an organic acid and an inorganic acid, either alone or in combination of two or more. An acid that becomes an anion and a base that becomes a cation may be added separately to the liquid.

[0044] Examples of the protic organic polar solvent that is the solvent include monohydric alcohols, polyhydric alcohols, and oxyalcohol compounds. Examples of the monohydric alcohols include ethanol, propanol, butanol, pentanol, hexanol, cyclobutanol, cyclopentanol, cyclohexanol, and benzyl alcohol. Examples of the polyhydric alcohols and oxyalcohol compounds include ethylene glycol, propylene glycol, glycerin, methyl cellosolve, ethyl cellosolve, methoxypropylene glycol, dimethoxypropanol, and alkylene oxide adducts of polyhydric alcohols such as polyethylene glycol and polyoxyethylene glycerin. Among these, ethylene glycol is preferred as the solvent. Ethylene glycol causes a change in the higher-order structure of the conductive polymer, resulting in good initial ESR characteristics and good high-temperature characteristics. It is even better if the ethylene glycol is 50 wt% or more in the liquid.

[0045] Representative examples of aprotic organic polar solvents that serve as solvents include sulfones, amides, lactones, cyclic amides, nitriles, and oxides. Examples of sulfones include dimethyl sulfone, ethyl methyl sulfone, diethyl sulfone, sulfolane, 3-methyl sulfolane, and 2,4-dimethyl sulfolane. Examples of amides include N-methylformamide, N,N-dimethylformamide, N-ethylformamide, N,N-diethylformamide, N-methylacetamide, N,N-dimethylacetamide, N-ethylacetamide, N,N-diethylacetamide, and hexamethylphosphoric amide. Examples of lactones and cyclic amides include γ-butyrolactone, γ-valerolactone, δ-valerolactone, N-methyl-2-pyrrolidone, ethylene carbonate, propylene carbonate, butylene carbonate, and isobutylene carbonate. Examples of the nitriles include acetonitrile, 3-methoxypropionitrile, glutaronitrile, etc. Examples of the oxides include dimethyl sulfoxide, etc.

[0046] Examples of organic acids that serve as anion components as solutes include carboxylic acids such as oxalic acid, succinic acid, glutaric acid, pimelic acid, suberic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, maleic acid, adipic acid, benzoic acid, toluic acid, enanthic acid, malonic acid, 1,6-decanedicarboxylic acid, 1,7-octanedicarboxylic acid, azelaic acid, resorcylic acid, phloroglucic acid, gallic acid, gentisic acid, protocatechuic acid, pyrocatechuic acid, trimellitic acid, and pyromellitic acid, as well as phenols and sulfonic acids. Examples of inorganic acids include boric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, carbonic acid, and silicic acid. Examples of composite compounds of organic acids and inorganic acids include borodisalicylic acid, borodioxalic acid, borodiglycolic acid, borodimalonic acid, borodisuccinic acid, borodiadipic acid, borodiazelaic acid, borodibenzoic acid, borodimaleic acid, borodilactic acid, borodimalic acid, boroditartaric acid, borodicitric acid, borodiphthalic acid, borodi(2-hydroxy)isobutyric acid, borodiresorcylic acid, borodimethylsalicylic acid, borodinaphthoic acid, borodimandelic acid, and borodi(3-hydroxy)propionic acid.

[0047] In addition, examples of at least one salt of an organic acid, an inorganic acid, and a complex compound of an organic acid and an inorganic acid include ammonium salt, quaternary ammonium salt, quaternary amidinium salt, amine salt, sodium salt, potassium salt, etc. Examples of quaternary ammonium ions of quaternary ammonium salts include tetramethylammonium, triethylmethylammonium, tetraethylammonium, etc. Examples of quaternary amidinium salts include ethyldimethylimidazolinium, tetramethylimidazolinium, etc. Examples of amine salts include salts of primary amines, secondary amines, and tertiary amines. Examples of primary amines include methylamine, ethylamine, propylamine, etc., examples of secondary amines include dimethylamine, diethylamine, ethylmethylamine, dibutylamine, etc., and examples of tertiary amines include trimethylamine, triethylamine, tributylamine, ethyldimethylamine, ethyldiisopropylamine, etc.

[0048] Further, other additives can be added to the liquid. Examples of additives include alkylene oxide adducts of polyhydric alcohols such as polyethylene glycol and polyoxyethylene glycerin, complex compounds of boric acid and polysaccharides (mannitol, sorbitol, etc.), complex compounds of boric acid and polyhydric alcohols, boric acid esters, nitro compounds (o-nitrobenzoic acid, m-nitrobenzoic acid, p-nitrobenzoic acid, o-nitrophenol, m-nitrophenol, p-nitrophenol, p-nitrobenzyl alcohol, etc.), and phosphoric acid esters. These may be used alone or in combination of two or more. The amount of additive added is not particularly limited, but it is preferable to add it to an extent that does not deteriorate the characteristics of the solid electrolytic capacitor, for example, 60 wt% or less in the liquid. Among the above additives, it is preferable to add alkylene oxide adducts of polyhydric alcohols, especially polyethylene glycol, and complex compounds of boric acid and polyhydric alcohols for the purpose of improving the withstand voltage, and to add nitro compounds for the purpose of absorbing gas in the capacitor.

[0049] Even if moisture is not intentionally added to solid electrolytic capacitors, moisture may be mixed in during the manufacturing process. The moisture content in solid electrolytic capacitors is preferably kept below 10 wt%, more preferably below 5 wt%. If the moisture content is high, the adhesion between the electrode foil and the solid electrolyte layer may deteriorate, leading to deterioration of the solid electrolyte layer and an increase in ESR. The reasons for moisture being mixed into solid electrolytic capacitors during the manufacturing process include moisture adhering to the separator and moisture in the air being mixed in.

[0050] (Electrolyte layer component ratio) First, the molar ratio of cations to 1 mol of functional groups that can contribute to the doping reaction of the dopant, which will be described below, is the molar ratio of cations to 1 mol of functional groups that can contribute to the doping reaction among the functional groups of the dopant. It is not necessary that all of the functional groups that can contribute to the doping reaction of the dopant are involved in the doping reaction of the conjugated polymer, and for example, a part of the functional groups that can contribute to the doping reaction may be doped, and the remaining part may not be doped. In addition, all of the functional groups that can contribute to the doping reaction of the dopant may be doped. That is, the molar ratio of the cationic component to 1 mol of functional groups that can contribute to the doping reaction is important, not the functional groups that are involved in the doping reaction among the functional groups of the dopant. Hereinafter, the functional groups that can contribute to the doping reaction of the dopant are referred to as doping functional groups. In addition, the cationic component is also simply referred to as a cation.

[0051] At least ammonia is added to the electrolyte layer as a cationic component. The combined molar ratio of all cations, including ammonia, in the electrolyte layer per 1 mol of dopable functional group is 23 or less. In this range, the ESR of the solid electrolytic capacitor is kept low even after thermal stress loading. Thermal stress loading refers to all situations in which thermal stress is applied to solid electrolytic capacitors, such as during the reflow process or when solid electrolytic capacitors are used in high-temperature environments.

[0052] Although not limited thereto, it is speculated that the ESR can be suppressed low when the molar ratio of the total of all cations including ammonia to 1 mol of dopable functional group is 23 or less for the following reason. That is, the cationic component neutralizes the dopant, transitions the conductive polymer from bipolaron to polaron, improves the conductivity of the conductive polymer, and reduces the ESR of the solid electrolytic capacitor. In addition, heat stress causes a first phenomenon in which the conductive polymer transitions from bipolaron to polaron by promoting the neutralization action of the cationic component on the dopant, and a second phenomenon in which the dopant de-doping reaction is easily caused by promoting the action of the cationic component on the dopant. It is speculated that the balance between the first and second phenomena is related to the molar ratio of the cationic component to 1 mol of the dopable functional group.

[0053] As a result, it is considered that if the molar ratio of cations to 1 mole of dopable functional groups is more than 11.4 and not more than 23, the second phenomenon caused by thermal stress is relatively suppressed and the effect of the first phenomenon caused by thermal stress remains, causing the conductive polymer to transition from bipolaron to polaron. On the other hand, if the molar ratio exceeds 23, the second phenomenon becomes predominant, and as a result, the ESR after thermal stress becomes large.

[0054] In particular, in the electrolyte layer, the molar ratio of cations to 1 mol of dopable functional groups is preferably 11.4 or less. If the molar ratio is greater than 6 and less than 11.4, the effect of the first phenomenon due to thermal stress load is greater, and the increase in the ESR of the solid electrolytic capacitor after thermal stress load is suppressed to be lower than the range of greater than 11.4 and less than 23, so that the ESR of the solid electrolytic capacitor can be maintained even lower even after thermal stress load. Furthermore, the molar ratio of cations to 1 mol of dopable functional groups is preferably greater than 2.8 and less than 6. If the molar ratio is greater than 2.8 and less than 6, the first and second phenomena due to thermal stress load are counterbalanced, and there is no change in the ESR of the solid electrolytic capacitor before and after thermal stress load, so that the ESR of the solid electrolytic capacitor can be maintained even lower even after thermal stress load.

[0055] Furthermore, the molar ratio of cations to 1 mol of dopable functional groups is preferably 2.8 or less. When the molar ratio is 2.8 or less, the first phenomenon caused by the thermal stress load prevails over the second phenomenon, and the ESR after the thermal stress load is kept equal to or lower than the ESR before the thermal stress load.

[0056] In addition, when at least ammonia is added as a cationic component, the molar ratio at which the first and second phenomena due to heat stress load are competitive, the molar ratio at which the influence of the first phenomenon due to heat stress load remains large, and the molar ratio at which the second phenomenon is dominant tend to shift in the larger direction, compared to when a cationic component other than ammonia is added. This is speculation, but it is thought that the undoping reaction is difficult to occur because ammonia has a low ability to form a salt with the dopant polystyrene sulfonic acid.

[0057] Here, the cationic components contained in the electrolyte layer are the total amount of cationic components contained in the electrolyte layer, regardless of whether they are derived from the liquid or the solid electrolyte layer, and ammonia may be contained in the liquid, the solid electrolyte layer, or both. Specifically, when the cationic components are contained in the solid electrolyte layer and the liquid does not contain the cationic components, the cationic components contained in the electrolyte layer are the cationic components derived from the solid electrolyte layer, and the total amount of the cationic components derived from the solid electrolyte layer is defined relative to 1 mol of the dopable functional group. In addition, when the cationic components are not contained in the solid electrolyte layer and the cationic components are contained in the liquid, the cationic components contained in the electrolyte layer are the cationic components derived from the liquid, and the cationic components in the liquid are defined relative to 1 mol of the dopable functional group. Furthermore, when the cationic components are contained in both the solid electrolyte layer and the liquid, the cationic components contained in the electrolyte layer are the total amount of the cationic components derived from the solid electrolyte layer and the cationic components derived from the liquid, and the total amount of the cationic components derived from the solid electrolyte layer is defined relative to 1 mol of the functional group that can contribute to the doping reaction of the dopant.

[0058] Ammonia may be contained in the liquid, the solid electrolyte layer, or both. In addition, the molar fraction of ammonia in all cationic components contained in the liquid and the solid electrolyte layer is preferably 0.1 or more, and more preferably, the molar fraction of ammonia in all cationic components contained in the liquid and the solid electrolyte layer is 0.5 or more. It is more preferable that the molar fraction of ammonia in all cationic components contained in the liquid and the solid electrolyte layer is 0.9 or more, and it is particularly preferable that the molar fraction is 1.0, that is, only ammonia. The ESR after thermal stress load changes significantly around each of the boundaries of the ammonia molar fraction of 0.1, 0.5, and 0.9, and when the ammonia molar fraction becomes 1.0, the ESR after thermal stress load is the best.

[0059] The dopable functional group is not particularly limited, and examples thereof include inorganic acids, sulfo groups, carboxy groups, and hydroxy groups. Here, electrical conductivity is exhibited by adding a small amount of an acceptor that easily accepts electrons or a donor that easily gives electrons to the conjugated polymer. When an acceptor or donor is added to a conjugated polymer, in the case of an acceptor, π electrons are extracted from the conjugated polymer to form a negatively charged simple substance (positive hole), and in the case of a donor, electrons are supplied to form a negatively charged carrier, thereby exhibiting electrical conductivity.

[0060] The electrolyte layer may contain anion components and cation components in equal amounts, may contain an excess of cation components compared to anion components, or may contain an excess of anion components compared to cation components. That is, the molar ratio of acid components and base components in the electrolyte layer may be any. As long as the amount of cation components contained in the electrolyte layer is specified relative to 1 mol of dopable functional groups, the ESR of the solid electrolytic capacitor can be kept low even after thermal stress loading, regardless of whether the anion components and cation components are equal in amount, the amount of cation components is excessive, or the amount of anion components is excessive.

[0061] (Separator) Examples of the separator include cellulose papers such as kraft, Manila hemp, esparto, hemp, and rayon, and mixed papers thereof; polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and derivatives thereof; polytetrafluoroethylene-based resins, polyvinylidene fluoride-based resins, vinylon-based resins, polyamide-based resins such as aliphatic polyamides, semi-aromatic polyamides, and fully aromatic polyamides; polyimide-based resins, polyethylene resins, polypropylene resins, trimethylpentene resins, polyphenylene sulfide resins, acrylic resins, and polyvinyl alcohol resins. These resins can be used alone or in combination. EXAMPLES

[0062] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0063] The amounts of cations and anions in the electrolyte layer were changed to produce solid electrolytic capacitors in Examples 1 to 21 and Comparative Example 1, and the capacitors were subjected to a thermal stress load by a reflow process, and the ESR was measured before and after the thermal stress load. The common features of each solid electrolytic capacitor are as follows.

[0064] That is, the anode foil was an aluminum foil, which was etched to enlarge the surface area and then chemically treated to form a dielectric oxide film. The cathode foil was a plain aluminum foil, i.e., an unetched aluminum foil. Lead wires were connected to each of the anode and cathode foils, and the anode and cathode foils were wound facing each other with a manila separator interposed between them. This resulted in a capacitor element with a diameter of 6.1 mm and a height of 6.3 mm. The capacitor element was then immersed in an aqueous solution of ammonium dihydrogen phosphate for 10 minutes to perform a restoration chemical conversion.

[0065] Next, polyethylenedioxythiophene (PEDOT) doped with polystyrene sulfonic acid (PSS) (PEDOT / PSS) was prepared, and ammonia was added as a cationic component according to each example and comparative example. A capacitor element was immersed in this dispersion, and the capacitor element was pulled out and dried at 150°C for 30 minutes. The immersion and drying were repeated twice. This formed a solid electrolyte layer on the capacitor element. After the solid electrolytic capacitor was produced, the amount of PEDOT / PSS in the solid electrolytic capacitor was measured and found to be about 0.6 mg.

[0066] In addition, azelaic acid, which is an anion component, and ammonia, which is a cation component, were added to ethylene glycol in accordance with each Example and Comparative Example to prepare a liquid. Then, the capacitor element on which the solid electrolyte layer was formed was immersed in the liquid. The capacitor element was inserted into a cylindrical exterior case with a bottom, and a rubber seal was attached to the open end and sealed by crimping.

[0067] Each solid electrolytic capacitor was subjected to aging treatment by applying a voltage. The rated capacitance of each of the produced solid electrolytic capacitors was 47 μF. The ESR of these solid electrolytic capacitors was measured before thermal stress loading at room temperature of 20° C. Then, in Examples 1 to 21 and Comparative Example 1, a reflow process was performed at a peak temperature of 260° C. in order to confirm the influence of thermal stress loading, and after leaving at room temperature, the ESR after the thermal stress loading by this reflow process was measured.

[0068] Here, the PSS used as the dopant was the same for all types of solid electrolytic capacitors. As shown in Table 1 below, the amount of ammonia contained in the solid electrolyte layer, the amount of azelaic acid contained in the electrolyte solution (liquid), and the amount of ammonia contained in the electrolyte solution (liquid) differ for each solid electrolytic capacitor. Therefore, as shown in Table 1 below, the molar ratio of the cationic components contained in the electrolyte layer to 1 mole of dopable functional groups differs for each solid electrolytic capacitor. The component ratios are shown in Table 1 below, along with the ESR of each solid electrolytic capacitor before and after reflow. In Table 1, "electrolyte solution" refers to "liquid."

[0069] [Table 1]

[0070] As shown in Table 1, in Examples 1 to 7 and Comparative Example 1, the cationic component was not added to the solid electrolyte layer, the amount of azelaic acid, which is an anionic component in the liquid, was fixed, and the amount of ammonia, which is a cationic component in the liquid, was changed from too little to an equal amount to an excess relative to the anionic component. In Examples 8 to 10, the cationic component was not added to the solid electrolyte layer, the amount of ammonia in the liquid was fixed, and the anionic component in the liquid was changed from not added to an excess relative to the ammonia. In Examples 11 to 17, the amount of ammonia, which is a cationic component of the solid electrolyte layer, was fixed, the amount of anionic component in the liquid was fixed, and the ammonia, which is a cationic component in the liquid, was changed from not added to an equal amount to an excess relative to the anionic component. In Examples 18 to 21, the amount of ammonia, which is a cationic component of the solid electrolyte layer, was changed, and the anionic component and cationic component in the liquid were not added.

[0071] FIG. 2 is a graph showing the relationship between the ESR before and after reflow in Table 1 and the molar ratio of ammonia, which is a cationic component, to 1 mol of dopable functional groups. In FIG. 2, the first series represents the change in ESR before reflow, and includes Examples 1 to 7 and Comparative Example 1 in which the anionic components in the liquid are fixed. The second series represents the change in ESR after reflow in the first series, and includes Examples 1 to 7 and Comparative Example 1 in which the anionic components in the liquid are fixed. The third series represents the change in ESR before reflow, and includes Examples 11 to 17 in which the amount of ammonia, which is a cationic component in the solid electrolyte layer, is fixed. The fourth series represents the change in ESR after reflow in the third series, and includes Examples 11 to 17 in which the amount of ammonia, which is a cationic component in the solid electrolyte layer, is fixed, and the amount of anionic components in the liquid is fixed. The fifth series shows the change in ESR before reflow, and includes Examples 18 to 21 in which the amount of ammonia, the cationic component in the solid electrolyte layer, was changed while no anionic or cationic components were added to the liquid. The sixth series shows the change in ESR after reflow in the fifth series, and includes Examples 18 to 21 in which the amount of ammonia, the cationic component in the solid electrolyte layer, was changed while no anionic or cationic components were added to the liquid.

[0072] Fig. 3 is a graph showing the relationship between the ESR before and after reflow in Table 1 and the molar ratio of ammonia, which is a cationic component, to 1 mol of functional groups contributing as a dopant. In Fig. 3, the first series shows the change in ESR before reflow, and includes Examples 8 to 10 in which the amount of ammonia, which is a cationic component in the electrolyte layer, is fixed and the amount of anionic components in the liquid is changed. In Fig. 3, the second series shows the change in ESR after reflow in the first series, and includes Examples 8 to 10 in which the amount of ammonia, which is a cationic component in the electrolyte layer, is fixed and the amount of anionic components in the liquid is changed.

[0073] As can be seen from Examples 1 to 7 and Comparative Example 1 in Table 1, and the second series in Figure 2, it can be confirmed that the ESR of the solid electrolytic capacitor after reflow increases with an increase in the amount of ammonia, which is a cationic component, rather than with the amount of anionic components. As can be seen from Examples 8 to 10 in Table 1, and Figure 3, it can be confirmed that the ESR of the solid electrolytic capacitor after reflow does not change when the amount of ammonia, which is a cationic component, is fixed, even if the amount of anionic components is changed.

[0074] Furthermore, as can be seen from a comparison of the first to fourth series in FIG. 2, the behavior of the change in ESR before and after reflow with respect to the change in the amount of cationic components is similar between the first and second series, and between the third and fourth series. This confirms that the ESR changes depending on the total amount of ammonia in the electrolyte layer, regardless of whether the ammonia is derived from the solid electrolyte layer or the liquid.

[0075] As shown in Table 1, FIG. 2 and FIG. 3, if the molar ratio of ammonia to 1 mol of dopable functional group is 2.8 or less, it can be confirmed that the ESR after reflow is equal to or lower than the ESR before reflow. If the molar ratio of ammonia to 1 mol of dopable functional group is more than 2.8 and less than 6, there is no change in the ESR of the solid electrolytic capacitor before and after the thermal stress load, and as a result, it can be confirmed that the ESR of the solid electrolytic capacitor can be maintained even lower after the thermal stress load. If the molar ratio of ammonia to 1 mol of dopable functional group is more than 6 and less than 11.4, the increase in the ESR of the solid electrolytic capacitor after the thermal stress load is suppressed, and as a result, it can be confirmed that the ESR of the solid electrolytic capacitor can be maintained even lower after the thermal stress load. If the molar ratio of ammonia to 1 mol of dopable functional group is more than 11.4 and less than 23, it can be confirmed that the ESR after the thermal stress load increases with the increase in the cationic component, but is still suppressed to about 23% compared to Comparative Example 1.

[0076] Next, solid electrolytic capacitors of Examples 22 to 27 containing ammonia and other cationic components in the electrolyte layer were prepared, and a thermal stress load was applied by a reflow process, and the ESR was measured before and after the thermal stress load. In the solid electrolytic capacitors of Examples 22 to 27, the cationic component contained in the solid electrolyte layer was sodium hydroxide, and the cationic component contained in the liquid was ammonia. The solid electrolytic capacitors of Examples 22 to 27 were prepared under the same conditions as Examples 1 to 21, except that the cationic component in the solid electrolyte layer was sodium hydroxide.

[0077] As shown in Table 2 below, the solid electrolytic capacitors of Examples 22 to 27 have a fixed amount of sodium hydroxide contained in the solid electrolyte layer and a fixed amount of azelaic acid contained in the electrolyte solution (liquid), but the amount of ammonia contained in the electrolyte solution (liquid) is different. Therefore, as shown in Table 2 below, each solid electrolytic capacitor has a different molar ratio of the total of cationic components contained in the electrolyte layer to 1 mole of dopable functional groups. The component ratios are shown in Table 2 below, along with the ESR of each solid electrolytic capacitor before and after reflow. In Table 2, "electrolytic solution" refers to "liquid."

[0078] [Table 2]

[0079] As shown in Table 2, in Examples 22 to 27, a fixed amount of sodium hydroxide, which is a cationic component, was added to the solid electrolyte layer, the amount of azelaic acid, which is an anionic component in the liquid, was fixed, and the amount of ammonia, which is a cationic component in the liquid, was changed from less than the anionic component to an equal amount, and then to an excess.

[0080] Fig. 4 is a graph showing the relationship between the ESR before and after reflow in Table 2 and the molar ratio of the cationic components, which are the sum of ammonia and sodium hydroxide, to 1 mol of the dopable functional group. In Fig. 4, the first series shows the change in ESR before reflow, and the second series shows the change in ESR after reflow of the first series.

[0081] As can be seen from Examples 22 to 27 in Table 2 and the second series in Figure 4, when ammonia is contained as a cationic component, even if other cationic components are added, it can be confirmed that the ESR after reflow of the solid electrolytic capacitor increases not with the amount of anionic components but with an increase in the amount of cationic components including ammonia.

[0082] Next, solid electrolytic capacitors of Examples 28 to 39 and Comparative Examples 7 to 9 were prepared by adding benzoic acid, 1,6-decanedicarboxylic acid, or phthalic acid as an anion component in the electrolyte, and a thermal stress load was applied by a reflow process. The ESR was measured before and after the thermal stress load. The results are shown in Table 3.

[0083] [Table 3]

[0084] As shown in Table 3, the solid electrolytic capacitors of Examples 28 to 31 and Comparative Example 7 were fabricated under the same conditions as Examples 1 to 7, except that the anion component contained in the liquid was benzoic acid and the amount of the cationic component ammonia was changed. The solid electrolytic capacitors of Examples 32 to 35 and Comparative Example 8 were fabricated under the same conditions as Examples 1 to 7, except that the anion component contained in the liquid was 1,6-decanedicarboxylic acid and the amount of the cationic component ammonia was changed. The solid electrolytic capacitors of Examples 36 to 39 and Comparative Example 9 were fabricated under the same conditions as Examples 1 to 7, except that the anion component contained in the liquid was phthalic acid and the amount of the cationic component ammonia was changed.

[0085] FIG. 5 is a graph showing the relationship between the ESR before and after reflow in Table 3 and the molar ratio of ammonia, which is a cationic component, to 1 mol of dopable functional groups. In FIG. 5, the first series shows the change in ESR before reflow, and includes Examples 28 to 31 and Comparative Example 7 in which the anion component in the liquid is benzoic acid and the amount of benzoic acid is fixed. The second series shows the change in ESR after reflow in the first series, and includes Examples 28 to 31 and Comparative Example 7 in which the anion component in the liquid is benzoic acid and the amount of benzoic acid is fixed. In FIG. 5, the third series shows the change in ESR before reflow, and includes Examples 32 to 35 and Comparative Example 8 in which the anion component in the liquid is 1,6-decanedicarboxylic acid and the amount of 1,6-decanedicarboxylic acid is fixed. The fourth series shows the change in ESR after reflow in the third series, and includes Examples 32 to 35 and Comparative Example 8 in which the anion component in the liquid was 1,6-decanedicarboxylic acid and the amount of 1,6-decanedicarboxylic acid was fixed. In FIG. 5, the fifth series shows the change in ESR before reflow, and includes Examples 36 to 39 and Comparative Example 9 in which the anion component in the liquid was phthalic acid and the amount of phthalic acid was fixed. The sixth series shows the change in ESR after reflow in the fifth series, and includes Examples 36 to 39 and Comparative Example 9 in which the anion component in the liquid was phthalic acid and the amount of phthalic acid was fixed.

[0086] As can be seen from Table 3 and FIG. 5, it can be confirmed that the ESR of the solid electrolytic capacitor after reflow increases with an increase in ammonia, which is a cationic component, regardless of the type of anionic component in the electrolyte layer.

[0087] And, if the molar ratio of ammonia to 1 mol of dopable functional group is 2.8 or less, it can be confirmed that the ESR after reflow is equal to or lower than the ESR before reflow. Also, if the molar ratio of ammonia to 1 mol of dopable functional group is more than 2.8 and less than 6, it can be confirmed that there is no change in the ESR of the solid electrolytic capacitor before and after the thermal stress load. Also, if the molar ratio of ammonia to 1 mol of dopable functional group is more than 6 and less than 11.4, it can be confirmed that the increase in the ESR of the solid electrolytic capacitor after the thermal stress load is suppressed. Also, if the molar ratio of ammonia to 1 mol of dopable functional group is more than 11.4 and less than 23, it can be confirmed that it is significantly suppressed compared to Comparative Examples 7 to 9.

[0088] From the above, the ESR of a solid electrolytic capacitor after thermal stress is related to the total amount of cationic components including ammonia in the electrolyte layer per 1 mol of functional groups that can contribute to the doping reaction of the dopant. If the molar ratio of the total of cationic components including ammonia is 23 or less, the ESR of the solid electrolytic capacitor after thermal stress is good. If the molar ratio of the total of cationic components including ammonia is 11.4 or less, the increase in ESR of the solid electrolytic capacitor after thermal stress can be suppressed. If the molar ratio of the total of cationic components including ammonia is 6 or less, the ESR of the solid electrolytic capacitor after thermal stress is maintained low. If the molar ratio of the total of cationic components including ammonia is 2.8 or less, the ESR of the solid electrolytic capacitor after thermal stress is suppressed to be equal to or lower than the ESR before thermal stress.

[0089] Furthermore, solid electrolytic capacitors of Comparative Examples 2 to 6 were prepared by adding triethylamine as a cationic component in the electrolyte layer, and were subjected to a thermal stress load by a reflow process, and the ESR was measured before and after the thermal stress load. The ESR was then compared with that of the solid electrolytic capacitors of Examples 1 to 7. The solid electrolytic capacitors of Comparative Examples 2 to 6 were prepared under the same conditions as Examples 1 to 7, except that the cationic component contained in the liquid was triethylamine. The results are shown in Table 4 below, together with those of Examples 1 to 7.

[0090] [Table 4]

[0091] As can be seen from Examples 1 to 3 and Comparative Examples 2 to 4 in Table 4, the ESR after reflow is suppressed to a low level without much difference whether the cationic component contains ammonia or is a cationic component other than ammonia, as long as the molar ratio of the cationic component to 1 mol of dopable functional group is 2.8 or less. On the other hand, as can be seen from Examples 4 to 7 and Comparative Examples 5 and 6 in Table 4, when the cationic component contains ammonia, the ESR after reflow continues to be significantly suppressed even if the molar ratio of the cationic component to 1 mol of dopable functional group is 5.6 or more and 23 or less. That is, when the cationic component contains ammonia, the ESR can be significantly suppressed until the molar ratio of the cationic component to 1 mol of dopable functional group is 23 or less.

[0092] On the other hand, the solid electrolytic capacitors of Examples 40 to 48, in which not only triethylamine but also ammonia was added as a cationic component in the electrolyte layer, were fabricated, and subjected to a thermal stress load by a reflow process, and the ESR was measured before and after the thermal stress load. The ESR was then compared with that of Comparative Example 5, in which only triethylamine was added, and that of Example 4, in which only ammonia was added. The results are shown in Table 5.

[0093] [Table 5]

[0094] As shown in Table 5, the solid electrolytic capacitors of Comparative Example 5, Examples 40 to 48, and Example 4 have different molar fractions of cationic components in the liquid. That is, the solid electrolytic capacitors of Examples 40 to 48 have molar fractions of triethylamine and ammonia that are changed in increments of 0.1 between the solid electrolytic capacitor of Comparative Example 5, in which the molar fraction of triethylamine is 1, and the solid electrolytic capacitor of Example 4, in which the molar fraction of ammonia is 1. The solid electrolytic capacitors of Comparative Example 5 and Examples 40 to 48 were fabricated under the same conditions as Example 4, except for this molar fraction.

[0095] Based on Table 5, the relationship between the ESR after reflow and the molar fraction of ammonia in all cationic components contained in the electrolyte (liquid) is shown in Figure 6. As can be seen from Table 5 and Figure 6, it was confirmed that if the electrolyte contains ammonia, the ESR after thermal stress loading can be kept low even if other cationic components are also contained. Moreover, it was confirmed that when the molar fraction of ammonia in all cationic components contained in the electrolyte layer is 0.1 or more, the ESR after thermal stress loading is greatly suppressed, and when the molar fraction is 0.5 or more, the ESR after thermal stress loading is further greatly suppressed, and when the molar fraction is 0.9 or more, the ESR after thermal stress loading is significantly suppressed, and a molar fraction of 1.0 is particularly preferable.

[0096] In order to confirm whether the tendency of ESR before and after the thermal stress load is similar even if the amount of PEDOT / PSS in the solid electrolytic capacitor is increased, the solid electrolytic capacitor of Example 28 was produced as follows. In Example 28, the solid electrolytic capacitor was produced by the same manufacturing method as in Example 12, except that the process of immersing the capacitor element in a dispersion liquid of a conductive polymer and drying was repeated six times. That is, the molar ratio of the cationic component to 1 mol of the dopable functional group in the solid electrolyte layer and in the electrolyte solution (liquid) is the same as in Example 12. After the solid electrolytic capacitor was produced, the amount of PEDOT / PSS in the solid electrolytic capacitor was measured and found to be 1.3 mg. The ESR at 20°C and the ESR after the reflow process at a peak temperature of 260°C were measured for the produced solid electrolytic capacitor in the same manner as in Example 12. The ESR was measured at 100 kHz.

[0097] In Example 28, the ESR before the thermal stress load was 0.05Ω, and the ESR after the thermal stress load was 0.05Ω, so the ESR before and after the thermal stress load was the same. In Example 12, the ESR before and after the thermal stress load was also the same. From this result, it was found that even if the amount of PEDOT / PSS was increased from 0.6mg to 1.3mg, the ESR before and after the thermal stress load was almost unchanged as long as the molar ratio of the cationic component to 1mol of the dopable functional group in the electrolyte layer was the same. Therefore, it was found that the tendency of the ESR before and after the thermal stress load was similar even if the amount of PEDOT / PSS was increased.

[0098] The manufacturing method of the solid electrolytic capacitor of the present application is not limited to the methods shown in the Examples. For example, the ESR of the solid electrolytic capacitor may be significantly reduced by adding an additive to the conductive polymer dispersion liquid or by increasing the number of repetitions of the process of immersing the capacitor element in the conductive polymer dispersion liquid and drying it.

[0099] In addition, the ESR of an electrolytic capacitor using only an electrolyte solution as an electrolyte is easily affected by the electrical conductivity of the electrolyte solution, and generally, the lower the electrical conductivity, the higher the ESR tends to be. However, the ESR of a solid electrolytic capacitor having a solid electrolyte layer and an electrolyte solution as in the present application is not easily affected by the electrical conductivity of the electrolyte solution. In other words, even if the electrical conductivity of the electrolyte solution is low, the ESR of the product can be sufficiently small. The reason for this is that the electrical conductivity of the conductive polymer used in the solid electrolytic capacitor is orders of magnitude higher than that of the electrolyte solution, and therefore the electrical conductivity of the conductive polymer has a large effect on the ESR.

Claims

1. a capacitor element formed by opposing an anode foil and a cathode foil; an electrolyte layer formed within the capacitor element; Equipped with The electrolyte layer is a solid electrolyte layer including a dopant and a conjugated polymer; a liquid filling a gap in the capacitor element in which the solid electrolyte layer is formed; and having the electrolyte layer contains cationic components in both the solid electrolyte layer and the liquid, the cationic component contained in the liquid includes ammonia, and the solid electrolyte layer includes the cationic component different from ammonia; a molar ratio of the cationic components contained in the solid electrolyte layer and the liquid to 1 mol of functional groups capable of contributing to a doping reaction of the dopant is 23 or less in total; A solid electrolytic capacitor characterized by:

2. the electrolyte layer contains the cationic component at a molar ratio of the cationic component to 1 mol of the functional group of 11.4 or less; 2. The solid electrolytic capacitor according to claim 1 .

3. the electrolyte layer contains the cationic component in a molar ratio of 6 or less to 1 mol of the functional group; 2. The solid electrolytic capacitor according to claim 1 .

4. the ammonia is contained in the electrolyte layer at a molar fraction of 0.1 or more of all cationic components in the electrolyte layer; 4. The solid electrolytic capacitor according to claim 1, wherein

5. the ammonia is contained in the electrolyte layer at a molar fraction of 0.5 or more of all cationic components in the electrolyte layer; 5. The solid electrolytic capacitor according to claim 4,

6. the dopant is polystyrene sulfonic acid; 6. The solid electrolytic capacitor according to claim 1,

7. the liquid comprises ethylene glycol; 7. The solid electrolytic capacitor according to claim 1,

8. The ethylene glycol is contained in the liquid at a content of 50 wt % or more.

8. The solid electrolytic capacitor according to claim 7,

9. A step of forming a capacitor element by opposing an anode foil and a cathode foil; forming an electrolyte layer within the capacitor element; Including, The step of forming the electrolyte layer includes: forming a solid electrolyte layer including a dopant and a conjugated polymer; filling a liquid into a void in the capacitor element in which the solid electrolyte layer is formed; having The electrolyte layer contains a cationic component in both the solid electrolyte layer and the liquid, The cationic component contained in the liquid is made to contain ammonia, and the cationic component different from ammonia is made to contain in the solid electrolyte layer; a molar ratio of the cationic components contained in the solid electrolyte layer and the liquid to 1 mol of functional groups capable of contributing to a doping reaction of the dopant is 23 or less in total; A method for producing a solid electrolytic capacitor comprising the steps of:

10. A method of forming a capacitor element, comprising: forming an electrolyte layer within the capacitor element; Including, The step of forming the electrolyte layer includes: forming a solid electrolyte layer including a dopant and a conjugated polymer; filling a liquid into a void in the capacitor element in which the solid electrolyte layer is formed; having The electrolyte layer contains ammonia as a cationic component, The cationic component is contained in both the solid electrolyte layer and the liquid, a molar ratio of the cationic components contained in the solid electrolyte layer and the liquid to 1 mol of functional groups capable of contributing to a doping reaction of the dopant is 23 or less in total; A method for producing a solid electrolytic capacitor comprising the steps of:

Citation Information

Patent Citations

  • Electrolytic capacitor

    JP2006114540A

  • Conductive polymer solid electrolytic capacitor

    JP2008218985A

  • Solid electrolytic capacitor and method for manufacturing the same

    JP2010505271A

  • Electronic component and manufacturing method of the same

    JP2012169575A

  • Electrolytic capacitor

    WO2011099261A1